Characterization of the secretomes of two vibrios pathogenic to mollusks. - Stéphanie Madec; Vianney Pichereau; Annick Jacq; Mathieu Paillard; Claire Boisset; Fabienne Guérard; Christine Paillard; Jean-Louis Nicolas (PLoS ONE, 2014)
Vibrio tapetis causes the brown ring disease in the Japanese clam Ruditapes philippinarum while Vibrio aestuarianus is associated with massive oyster mortalities. As extracellular proteins are often associated with the virulence of pathogenic bacteria, we undertook a proteomic approach to characterize the secretomes of both vibrios. The extracellular proteins (ECPs) of both species were fractionated by SEC-FPLC and in vitro assays were performed to measure the effects of each fraction on hemocyte cellular parameters (phagocytosis and adhesion). Fractions showing a significant effect were subjected to SDS-PAGE, and proteins were identified by nano LC-MS/MS. 45 proteins were identified for V. aestuarianus and 87 for V. tapetis. Most of them belonged to outer membrane or were periplasmic, including porins or adhesins that were already described as virulence factors in other bacterial species. Others were transporter components, flagella proteins, or proteins of unknown function (14 and 15 respectively). Interestingly, for V. aestuarianus, we noted the secretion of 3 extracellular enzymes including the Vam metalloprotease and two other enzymes (one putative lipase and one protease). For V. tapetis, we identified five extracellular enymes, i.e. two different endochitinases, one protease, one lipase and an adhesin. A comparison of both secretomes also showed that only the putative extracellular lipase was common to both secretomes, underscoring the difference in pathogenicity mechanisms between these two species. Overall, these results characterize for the first time the secretomes of these two marine pathogenic vibrios and constitute a useful working basis to further analyze the contribution of specific proteins in the virulence mechanisms of these species.